Does Anesthetic Relief Correspond to Future Pain Relief?: A Prospective Trial Examining Future Pain Relief for Ultrasound-Guided Corticosteroid-Anesthetic Injections. (12th November 2022) - Cushman, Daniel M.; Knox, Jordan; Kobayashi, Jacqueline K.; Zarate, Marisol; Wheelwright, John C.; Monson, Nicholas; English, Joy; Teramoto, Masaru
Abstract : Objectives: The aim of the study was to prospectively evaluate the association between immediate pain relief from injections of local anesthetic with corticosteroid and subsequent pain relief up to 3 mos. The secondary aim was to examine the time until subjective pain relief after these injections. Design: This was a single-center, prospective study of patients undergoing ultrasound-guided corticosteroid injections for musculoskeletal pain. Subjects completed follow-up surveys at 2 wks, 1 mo, and 3 mos postinjections. χ 2 tests and sensitivity analysis were used to examine the primary outcome, at least 50% relief from the injection. Regression modeling examined the effects of demographic and injection-related variables on outcome measures. Results: A total of 132 patients were enrolled (55% female, mean age 52 yrs). Response rates were 87.1% at 2 wks and 77.2% at 3 mos. The positive likelihood ratios from 50% initial pain relief ranged from 1.22 to 1.29 at the three time points, whereas the negative likelihood ratios ranged from 0.54 to 0.63. More than 75% of participants reported subjective pain relief by day 4 after injection. Conclusions: The predictive value of immediate pain relief for subsequent longer-term pain relief from corticosteroid-anesthetic injections is not particularly high. Most patients will obtain pain relief within 4 days of a corticosteroid injection.